Dieting the danger point - White, Brad (Del Mar, Calif. : CRM/McGraw-Hill Films, 1979)
Examines the physical and psychological dangers of current upsurge in the diseas known as anorexia nervosa. Explain how an epidemic nuber of today's bright, healty teenagers are willfully starving and over-exercising in the persuit of a slender figure. Shows the effects such behaviour has on the individuals and their families
Keywords: Anorexia nervosa